Automation of calculations significance of influence parameters in the manufacturing processes - Skoczylas, Leszek; Skoczylas, Krystyna (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2016)
The paper draws attention to the effort calculations occurring in the study signifi cance of infl uence parameters in the manufacturing processes. It presents original software for fast and accurate calculations according to the procedures for the static randomized programs – complete, block and latin square. The layout of the software directly responsible scheme of conduct contained in the literature. This approach does not require additional learning support of commercial software, and facilitates analysis. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)